Mapping the Ethics of Learning Analytics in Higher Education: A Systematic Literature Review of Empirical Research - Cerratto Pargman, Teresa; McGrath, Cormac (Journal of Learning Analytics, 2021)
Ethics is a prominent topic in learning analytics that has been commented on from conceptual viewpoints. For a broad range of emerging technologies, systematic literature reviews have proven fruitful by pinpointing research directions, knowledge gaps, and future research work guidance. With these outcomes in mind, we conducted a systematic literature review of the research on ethical issues that have been empirically approached in the learning analytics literature. In our final analysis, 21 articles published in the period 2014–2019 met our inclusion criteria. By analyzing this data, we seek to contribute to the field of learning analytics by 1) characterizing the type of empirical research that has been conducted on ethics in learning analytics in the context of higher education, 2) identifying the main ethical areas addressed in the selected literature, and 3) pinpointing knowledge gaps.